Search for Antimicrobial Activity Among Fifty-Two Natural and Synthetic Compounds Identifies Anthraquinone and Polyacetylene Classes That Inhibit Mycobacterium tuberculosis - Pollo, Luiz A. E.; Martin, Erlon F.; Machado, Vanessa R.; Cantillon, Daire; Wildner, Leticia Muraro; Bazzo, Maria Luiza; Waddell, Simon J.; Biavatti, Maique W.; Sandjo, Louis P. (Frontiers in Microbiology, 2021)
Drug-resistant tuberculosis threatens to undermine global control programs by limiting treatment options. New antimicrobial drugs are required, derived from new chemical classes. Natural products offer extensive chemical diversity and inspiration for synthetic chemistry. Here, we isolate, synthesize and test a library of 52 natural and synthetic compounds for activity against Mycobacterium tuberculosis. We identify seven compounds as antimycobacterial, including the natural products isobavachalcone and isoneorautenol, and a synthetic chromene. The plant-derived secondary metabolite damnacanthal was the most active compound with the lowest minimum inhibitory concentration of 13.07 µg/mL and a favorable selectivity index value. Three synthetic polyacetylene compounds demonstrated antimycobacterial activity, with the lowest MIC of 17.88 µg/mL. These results suggest new avenues for drug discovery, expanding antimicrobial compound chemistries to novel anthraquinone and polyacetylene scaffolds in the search for new drugs to treat drug-resistant bacterial diseases.